Strategi Komunikasi Islam dalam Pembinaan Akhlak pada Siswa di SMP Islam Terpadu (IT) Anugrah Hidayah Kecamatan Tamalate Kota Makassar - Yusuf Hamdani; Abd Rasyid Masri; St. Rahmatiah (Danudirja Setyabudi Nusantara, 2026)
Character education for students in the digital age faces complex challenges due to technological advancements, globalization, and shifting moral values among the younger generation. This study aims to identify and analyze Islamic communication strategies applied in character education for students at SMP IT Anugrah Hidayah in Makassar, as well as to identify supporting and hindering factors in their implementation. This study employs a qualitative approach with a phenomenological design. Data were collected through observation, in-depth interviews with the principal, teachers, and students, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results of the study indicate that SMP IT Anugrah Hidayah implements five forms of Islamic communication strategies in character development: (1) dialogue and discussion based on the principles of qawlan layyina, qaulan maisura, and qaulan ma’rufan; (2) exemplary behavior by the principal, teachers, and educational staff through the application of qawlan sadidan; (3) the regular implementation of religious activities such as morning Quran recitation (tadarus), Dhuha prayer, and “Blessed Friday” activities; (4) advice and guidance using the qawlan karima approach; and (5) educational discipline through administrative sanctions, a violation point system, and the Wajib Santri program. Supporting factors include cooperation between teachers and parents, emotional closeness between teachers and students, and positive responses from students. Meanwhile, inhibiting factors include a lack of parental attention, the influence of negative peer groups, and unrestricted use of digital media without adequate supervision. The Islamic communication strategies implemented have proven effective in shaping students’ character with noble morals through a holistic approach that integrates verbal, nonverbal, and transpersonal communication.